ANALISIS NASIKH MANSUKH PADA HADIS PUASA ASYURA RIWAYAT BUKHARI-MUSLIM - Lisdayanti Destiyani; Romlah Abu Bakar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
This study analyzes the concept of nasikh mansukh in hadiths on the fast of Ashura, focusing on the quality of the sanad (chain of transmission), the chronological phases of the legal establishment, and the comparative views of scholars from four main schools of thought. Using a qualitative descriptive-analytical approach, this study explores primary sources from Sahih al-Bukhari and Sahih Muslim, supplemented by books on hadith analysis, and comparative fiqh literature. The results show that the hadith of Ibn Abbas (Bukhari no. 2004) and the hadith of Aisha (Muslim no. 1125) represent two distinct legal phases, not actual contradictions: the first phase establishes the obligation of the fast of Ashura when the Prophet Muhammad (peace be upon him) arrived in Medina, and the second phase confirms the abolition of the obligation after the revelation of the Qur'anic verses on the fast of Ramadan (QS. Al-Baqarah: 183–185) in the second year of Hijriah. The nasikh process takes place through two complementary mechanisms: nasikh al-sunnah bil-sunnah (removal of the sunnah by the sunnah) and nasikh al-sunnah bil-Qur'an (removal of the sunnah by the Qur'an). The four schools of thought, Hanafi, Maliki, Syafi'i, and Hanbali, agree that the fast of Ashura now has the status of sunnah mu'akkadah (highly recommended), although there are differences of opinion regarding whether a formal obligation ever applied before. This research confirms that the Nasakh Mansukh framework is an irreplaceable methodological instrument in resolving apparent contradictions in hadith and understanding the way Islamic law slowly developed and changed.